Analisis Hubungan Tingkat Kerentanan Penduduk Wilayah Pantai Kota Semarang Akibat Banjir Rob dengan Status Kesehatan - Fiona Faiqoh; Sulistyani Sulistyani; Budiyono Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2017)
Tidal inundation always occurs every year in Semarang City and it has been threatening Semarang for years, especially the northern area of Semarang. One of the areas that exposed the most by tidal inundation and has a high severity level is Kelurahan Bandarharjo. Tidal inundation in that area can result in a wide variety of impacts in various aspects, particularly in terms of health aspect. The negative impacts of tidal inundation will increase the vulnerability of coastal communities to tidal inundation. A vulnerability is the degree to which a system is susceptible to, and unable to cope with adverse impacts of environmental change. There are three components of vulnerability, which are exposure, sensitivity and adaptive capacity. This study aims to analyze the relationship between the vulnerability index due to tidal flood and health status of coastal communities in Semarang. The research design conducted in this study was descriptive analitics study with cross sectional approach. The sample of this study is 92 inhabitants of RW 01 Kelurahan Bandarharjo. The results showed that the average index of exposure, sensitivity, adaptive capacity and vulnerability due to tidal inundation is moderate. Also, there is no significant correlation between exposure index (p = 0,389) and adaptive capacity index (0,071) with health status. While, sensitivity index (p = 0,007) and vulnerability index (p = 0,001) showed a significant correlation with health status. The conclusion of this study is the vulnerability of communities due to tidal inundation affects their health status negatively.